Structural behaviour of distressed and strengthened post-tensioned box beams - Ohu, Rachael Bukola; Thanoon, Waleed Abdulmalik; Noorzaie, Jamaloddin; Abdul Kadir, Mohd Razali; Jaafar, Mohd Saleh (ACC Limited, 2009)
This study focuses on the behaviour of post-tensioned box beams with snapped prestress cables. It also includes an investigation into the effectiveness of using select strengthening methods on distressed box beams. All beams were subjected to flexural-shear-torsional loads. The results show that snapping 15% of the prestressing cable area resulted in a 74% increase in deformation at service load and a 22% decrease in ultimate load. The snapping of prestress wires also increased the stresses in the snapped cables by 70%. All the strengthening techniques used effectively restored the beam performance at service and overcame the effect of cable snapping.